Thioxanthone-benzotriazole: Initiator and stabilizer properties in one component - Sevinc, Duygu; Karasu, Feyza; Arsu, Nergis (ELSEVIER SCIENCE SA, 2009)
The initiation efficiency of 3H-5-Thia-1,2,3-triaza-cyclopenta[b]-10-one (TX-BT) for free radical polymerization of methyl methacrylate (MMA), is enhanced by the addition of N-methyldiethanolamine (MBEA) to the initiator formulation. Photodegradation of polymethylmethacrylate (PMMA), which was prepared with and without TX-BT, was examined according to its weight loss. The beneficial effects of TX-BT as initiator and stabilizer for polymerization of methyl methacrylate was determined. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Phorostabilizer; Photoinitiator; Berzotriazole; Thioxanthone; QUANTUM YIELD; PHOTOSTABILIZATION; POLYMERIZATION; SOLVENT; Chemistry